ChemInform Abstract: Regioselective 1, 4‐ over 1, 2‐Addition of 3, 3‐Bis(silyl) Allyloxy Lithium to Enals, Enones and Enoates. The Remarkable α‐Effect of Silicon. Issue 42 (14th October 2014) - Ye, Xincui; Sun, Xianwei; Huang, Zhenggang; Yang, Na; Su, Zhishan; Hu, Changwei; Song, Zhenlei
Abstract The addition of 3, 3‐bis(silyl)allyloxy lithium, generated from enol ether (II), to α, β‐unsaturated carbonyl compounds such as (I), (IV), (VI), and (VIII), proceeds in an 1, 4‐ over 1, 2‐manner with medium to good regioselectivity, whereas the parent allyloxy lithium species undergoes complete 1, 2‐addition.